Evaluation of the accuracy of different system torque limiting devices - Mesut Köksal; Murat Kurt; Fuat Altuncu (BMC Oral Health)
Abstract Background As evaluating the accuracy of friction and spring type mechanical torque limiting devices (MTLDs), no previous study has eliminated eliminated operator-related error. The purpose of this study is to compare and evaluate the accuracy of different types of MTLDs without operator error. Materials and methods 2 friction-type and 3-spring type were selected to evaluate accuracy of MTLDs. A total of 25 new and calibrated MTLDs, five from each manufacturer, were used for the study. To prevent operator-related errors, a device, designed by the authors and manufactured by Bahadır Medical Instruments Inc.(Sabanoglu Organized Industrial Zone, Registiration No 3003717943, Samsun, Türkiye), was used. This device is capable of simulating the dentist’s hand push movement on the torque-limiting device. A Digital torque meter was positioned on the pins located on the bottom plate of the device. After being integrated into the mechanism, each MTLD was tested 10 times. The data were transferred to the computer owing to software Mesur gauge. Non-parametric statistical methods were frequently used in this study, since it was determined that both absolute percent deviation (PerDev) and ​the peak torque values did not match up to the normal distribution, based on the Shapiro Wilk test results. The Wilcoxon signed rank test was used to evaluate the initial accuracy of the devices. The bonferroni test was used for multiple comparisons. Finally, the Mann-Whitney U test was used to compare the performance of spring and frictional MTLDs (95% confidence interval for all statistical analyses). Results According to the wilcoxon signed rank test, there was no significant difference between the target torque and the peak torque values for any of the MTLDs (p > 0.05). While Medentika showed the highest PerDev, Straumann showed the lowest. Spring type MTLDs showed more accurate results than the friction type MTLDs (p < 0.05). Conclusion All devices showed peak torque values close to the target torque. However, spring type devices showed more accurate results than friction type devices.